High-Performance Carbon Nanotube Optoelectronic Transistor With Optimized Process for 3D Communication Circuit Applications - Shuang Liu; Heyi Huang; Yanqing Li; Yadong Zhang; Feixiong Wang; Zhaohao Zhang; Qingzhu Zhang; Jiali Huo; Jiaxin Yao; Jing Wen; Huaxiang Yin (IEEE Journal of the Electron Devices Society)
One-dimensionalcarbon nanotube field-effect transistors (CNFETs) have offered a solution for obtaining high transistor performance in a compatible low-temperature BEOL process, enabling monolithic 3D integration benefits for more functional circuits. Currently, CNT transistors need to further improve their performance with a more stable process and explore the most suitable circuit application scene. In this study, we successfully enhanced the performance of CNFETs through special Y2O3 film passivation and vacuum annealing processes. The on-state current of the optimized device was improved by $36.6× $ compared to the device without these processes. Besides, the subthreshold swing (SS) was notably reduced from 259 mV/dec to 215 mV/dec and the threshold voltage was decreased from 2.02 V to 1.79 V due to the reduction of the interface state. Meanwhile, the devices’ optoelectronic characteristics were significantly improved and exhibited a $72× $ increase in $Δ $ Ids under identical illumination. With an improved annealing process, the $Δ $ Ids were further increased to $231× $ compared to the original device because of the reduction of defects within the device. Finally, the tentative Morse code communication applications all by the optimized CNFETs were obtained. These technologies and functional implementations provided a promising approach for future 3D functional communication systems with CNT technology.